235U capture cross-section adjustment in criticality benchmarks using ENDF/B-VII.1 evaluation. Issue 1 (2nd January 2019) - Makhloul, M.; Boukhal, H.; Kaddour, M.; Chakir, E.; Maged, M.; Abdulaziz, A.
ABSTRACT: This present study aims to evaluate the nuclear data uncertainty on the neutron multiplication factor ( k eff ) in order to adjust the 235 U capture multigroup cross sections and the covariance matrix of the ENDF/B-VII.1 evaluation. For this purpose, the generalized linear-least squares method is applied. The 44 multigroup cross sections and the covariance matrix are processed with NJOY99 nuclear software, while MCNP6.1 nuclear code is used for the k eff and sensitivity profile calculations. The obtained results show that the 235 U capture cross sections require an adjustment of approximately −1% in 0–6 eV, −0.5% in 6 eV to 3 keV, 2% in 3 keV to 0.4 MeV, and −10% in 0.4–20 MeV.